2019
DOI: 10.1002/alr.22462
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis precipitated by tumor necrosis factor alpha inhibitors is the phenotype of chronic rhinosinusitis without nasal polyps

Abstract: BackgroundChronic rhinosinusitis (CRS) is a frequently observed condition in patients with immunodeficiency secondary to tumor necrosis factor alpha inhibitors (TNFαis). The histologic features of CRS caused by TNFαis have yet to be determined and may have important implications in understanding the pathophysiology of the disease process.MethodsA structured histopathology report was used to analyze sinus tissue removed during functional endoscopic sinus surgery (FESS). These structured histopathology variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The varied medical therapies to treat CRSsNP, including antibiotics and systemic corticosteroids, can also cause serious complications and add morbidity to the disease 1318–1323 . Interestingly, recent evidence suggests that CRSsNP can be precipitated by treatment with anti‐tumor necrosis factor‐alpha inhibitors for rheumatic conditions 1291,1324,1325 …”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…The varied medical therapies to treat CRSsNP, including antibiotics and systemic corticosteroids, can also cause serious complications and add morbidity to the disease 1318–1323 . Interestingly, recent evidence suggests that CRSsNP can be precipitated by treatment with anti‐tumor necrosis factor‐alpha inhibitors for rheumatic conditions 1291,1324,1325 …”
Section: Chronic Rhinosinusitis Without Nasal Polyps (Crssnp)mentioning
confidence: 99%
“…30 Furthermore, ovalbumin-sensitized mice lacking TNFα show marked reduction in nasal symptoms and Th2 cytokine mRNA expression following intranasal allergen challenge. 31 Of note, systemic anti-TNFα therapy has been reported to cause CRS, 32 suggesting that strategies targeting TNFα in CRS may need to be either locally administered or selectively target a downstream effector of TNFα. TNFα is a known potent inducer of nitric oxide synthase expression in macrophages 33 and bronchial epithelial cells, 34 but whether TNFα directly regulates NO production in upper airway respiratory cells remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphism of the TNFα‐1031 gene might be significantly correlated with the incidence of atopic CRS 34 . Peter et al 35 . classified patients with CRS treated with TNF‐α inhibitors into a separate subtype and also found that CRS on TNF‐α inhibitors (TNFαis) significantly reduced the number of eosinophils when compared to patients with CRSwNP.…”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%